Correlation between miR-210 and serum levels of GGT, ALP and AST in patients with choledocholithiasis: miR-210 correlation with GGT, ALP, AST in choledocholithiasis patients - Luo, Ping; Huang, Kun; Wu, Diqing; Xu, Hui (Cellular and Molecular Biology, 2024)
The purpose of this study was to explore the association between miR-210 and serum GGT, ALP and AST levels in patients with choledocholithiasis. The clinical data of 82 patients with biliary stones admitted to the hospital from May 2020 to May 2022 were collected and divided into observation group (n=40) and control group (n=42) according to whether asymptomatic combined. The relative expression level of miR-210 was measured by RT-PCR, serum GGT, ALP, and AST by rate method, and the correlation of miR-210 expression level with serum GGT, ALP, AST and the diagnostic value for choledochal stones was analyzed. The relative expression of serum GGT, ALP, AST and miR-210 were all higher than the control group (P <0.05); the relative expression level of miR-210 and serum GGT, ALP and AST, 0.756, 0.832, 0.326, r = P <0.05), 0.782, 0.776, 0.681, 0.568, respectively. Serum miR-210 level was upregulated in patients with choledocholithiasis, and its expression was positively correlated with serum GGT, ALP, and AST, which can be used for early auxiliary diagnosis of choledocholithiasis.